Prevalence, Incidence and Perceived Predisposition to Kidney Disease among Nigerian Population Resident in Lagos State, Nigeria: A Community-based Cross-sectional Study (African Journal of Biomedical Research, 2023)
Kidney disease (KD) development or progression is poorly characterized, and little is known about perceived predisposition to KD in Nigeria. This study aimed to determine the prevalence, incidence and perceived predisposition to KD among Nigerians with/without knowledge of kidney ailments, resident in Lagos State. A cross-sectional study of 1,757 respondents was recruited from the general population in Lagos State, Nigeria. Following informed consent, a questionnaire was used to gather demographic, lifestyle practices, and perceived predisposition to KD. Morbidity details of diagnosed kidney victims were also collected. Data were analyzed using SPSS version 22.0. A total of 1,757 respondents were studied, mean age of 33.83±11.54 (18-85+ years). Males comprised 932 (53.0%) while 825 (47.0%) were females. The frequency of lifestyle risk factors of KD observed were regular use of herbal drink in 816 (46.4%), chronic alcohol ingestion in 584 (33.2%), habitual use of herbal supplement in 471 (26.8%) and frequent consumption of grain foods in 1437 (81.8%) subjects. Respondents with knowledge of KD had lower perceived predisposition (83.2%) than their counterparts without knowledge of KD, while prevalence (1.9%) and incidence (0.3%) of KD was demonstrated respectively. Age group (p=0.014), cigarette smoking (p=0.02) and food groups (grain and junk foods) (p